Freedom of Speech in Post-Reform Indonesia: A Lawfare Perspective - Dang Perkasa Alam Panjaitan; Bhawika Tanggwa Prabhuttama (Fakultas Hukum Universitas Gadjah Mada, 2026)
This paper examines the use of lawfare as a mode of governance affecting freedom of speech in post-Reformasi Indonesia. While constitutional amendments to the 1945 Constitution formally entrenched freedom of speech, legal mechanisms have increasingly been mobilized to regulate, discipline, and suppress both political and social expression. Drawing on doctrinal legal analysis and political–institutional theory, the article argues that lawfare in Indonesia operates not primarily through overt censorship, but through strategic deployment of criminal, civil, and administrative law, particularly under the Electronic Information and Transactions Law, defamation provisions, and blasphemy regulations. Through analysis of prominent cases such as Deddy Febrianto Holo and Daniel Tangkilisa, Newmont Nusa Tenggara, Riau Andalan Pulp and Paper (RAPP) v. Tempo, Basuki Tjahaja Purnama, alongside Constitutional Court jurisprudence on freedom of speech, the article demonstrates how complaint-driven prosecutions, prosecutorial discretion, and judicial restraint collectively produce a chilling effects on journalists, activists, academics, and political opponents. These practices blur the boundary between legitimate regulation and political repression, embedding coercion within formally lawful processes. The article contributes to Southeast Asian governance scholarship by conceptualizing Indonesian lawfare as a form of legal–institutional power that reshapes democratic contestation while maintaining constitutional legality. It concludes by outlining normative criteria and institutional reforms to reconcile Pancasila-based public order with meaningful protection of freedom of speech.